2016
DOI: 10.1155/2016/8274689
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Treatment Prevents Sedentariness Related Damages in Mice

Abstract: Metformin (METF), historical antihyperglycemic drug, is a likely candidate for lifespan extension, treatment and prevention of sedentariness damages, insulin resistance, and obesity. Skeletal muscle is a highly adaptable tissue, capable of hypertrophy response to resistance training and of regeneration after damage. Aims of this work were to investigate METF ability to prevent sedentariness damage and to enhance skeletal muscle function. Sedentary 12-week-old C57BL/6 mice were treated with METF (250 mg/kg per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 38 publications
3
36
0
2
Order By: Relevance
“…It is known that loss of muscle mass impairs the ability to perform daily tasks, increases the incidence of injuries and could be a major risk factor of chronic diseases. 29 The current study showed that rats fed with HFD for 16 weeks gained more body weight and visceral fat when compared with chow fed group. 4 Met is a suggested candidate for lifespan extension, treatment and prevention of sedentariness damages, insulin resistance, and obesity.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…It is known that loss of muscle mass impairs the ability to perform daily tasks, increases the incidence of injuries and could be a major risk factor of chronic diseases. 29 The current study showed that rats fed with HFD for 16 weeks gained more body weight and visceral fat when compared with chow fed group. 4 Met is a suggested candidate for lifespan extension, treatment and prevention of sedentariness damages, insulin resistance, and obesity.…”
Section: Discussionmentioning
confidence: 48%
“…29 Besides, lowering lactate levels in rats, 38 Met decreased the expression of multiple collagen genes indicating its role in attenuation of extracellular matrix (ECM) dysregulation. Met was reported to maintain skeletal muscle mass through activation of AKT.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, highintensity or prolonged exercise (like running a marathon) is known to deplete the immune response, mainly due to the increase in endogenous cortisol [37]. The basic cellular mechanism via which physical exercise exerts most of its effect is an activation of AMP-kinase [38].…”
Section: Is There An Immunomodulatory Therapy To Prevent Influenza?mentioning
confidence: 99%
“…Although rapamycin has been associated with the prevention of age-related diseases and the extension of lifespan in both, obese and lean mice (Liu et al, 2014) and to avoid hyperlipidemia and diabetes-like syndrome in aged obese rats , a recent paper indicate that rapamycin reduces lifespan in the obese db/db mice . In the case of metformin, it has been associated with the prevention of sedentarism-dependent damages (Senesi et al, 2016).…”
Section: Mitochondrial Turnover Can Be Regulated By Different Factorsmentioning
confidence: 99%